Plasmodium falciparum Plasmepsin 2 Duplications, West Africa - Inoue, Juliana (2018)
Dihydroartemisinin/piperaquine (DHA/PPQ) is increasingly deployed as antimalaria drug in Africa. We report the detection in Mali of Plasmodium falciparum infections carrying plasmepsin 2 duplications (associated with piperaquine resistance) in 7/65 recurrent infections within 2 months after DHA/PPQ treatment. These findings raise concerns about the long-term efficacy of DHA/PPQ treatment in Africa.